Development and Psychometric Evaluation of the Lung Cancer Screening Health Belief Scales - Carter-Harris, Lisa (Cancer Nurs, 2017)
BACKGROUND: Lung cancer screening is a recent recommendation for long-term smokers. Understanding individual health beliefs about screening is a critical component in future efforts to facilitate patient-provider conversations about screening participation. OBJECTIVE: To describe the development and psychometric testing of four new scales to measure lung cancer screening health beliefs (perceived risk, perceived benefits, perceived barriers, self-efficacy). METHODS: In Phase 1, four scales were developed from extensive literature review, item modification from existing breast and colorectal cancer screening health belief scales, focus groups with long-term smokers, and evaluation/feedback from a panel of 10 content experts. In Phase 2, we conducted a survey of 497 long-term smokers to assess the final scales’ reliability and validity. RESULTS: Phase 1: Content validity was established with the content expert panel. Phase 2: internal consistency reliability of the scales was supported with Cronbach’s alphas ranging from .88 to .92. Construct validity was established with confirmatory factor analysis and testing for differences between screeners and non-screeners in theoretically-proposed directions. CONCLUSIONS: Initial testing supports the scales are valid and reliable. These new scales can help investigators identify long-term smokers more likely to screen for lung cancer and are useful for the development and testing of behavioral interventions regarding lung cancer screening. IMPLICATIONS FOR PRACTICE: Development of effective interventions to enhance shared decision-making about lung cancer screening between patients and providers must first identify factors influencing the individual’s screening participation. Future efforts facilitating patient-provider conversations is better informed by understanding the perspective of the individual making the decision.